Virtual reality system for 3D navigation with simulated prosthetic vision - Santos Villafranca, María; Pérez Yus, Alejandro; Bermúdez Cameo, Jesús; Guerrero, José J. (Jornada de Jóvenes Investigadores del I3A, 2022)
Recent advances in visual prostheses have demonstrated that it is possible to restore part of the vision in certain cases of visual impairment, yet with limitations such as low resolution or a reduced field of view. To experiment more easily, visual prosthesis simulators (VPS) are used. An immersive, flexible and realistic SPV is presented using a virtual reality system, so that environments created by a computer can be explored by integrating the real movement of the user’s head in the simulation thanks to the virtual reality goggles Oculus Rift DK2 and allowing a movement through the scenario using a controller or joystick in order to explore the environment as completely and realistically as possible.